Bio–relevant characterisation of lipidic formulations and prediction of in vivo exposure - Benito-Gallo, Paloma (2017)
Lipidic formulations (LFs) are increasingly utilised for the delivery of poorly–water soluble drugs to improve oral bioavailability. In vitro lipolysis is capable of mimicking the lipid digestion process and therefore it is a suitable method for assessing the fate of drugs administered in LFs. Intestinal micellar solubilisation and first–pass metabolism are the main contributors to the oral bioavailability of drugs that belong to class II of the Biopharmaceutics Classification System (BCS). The intraluminal solubility of BCS II drugs in LFs can be estimated with the in vitro lipolysis model, whereas the first–pass extraction ratio can be assessed by performing microsomal stability assays. This thesis work proposes, for the first time, the combination of in vitro lipolysis and microsomal metabolism studies for the quantitative prediction of human oral bioavailability of BCS II drugs administered in LFs. Marinol® (Δ9–tetrahydrocannabinol dissolved in sesame oil) and Neoral® (a lipidic self–emulsifying drug delivery system of cyclosporin A), were selected as model LFs. The observed oral bioavailability (Fobserved) values were obtained from published clinical studies that described the oral administration of the selected LFs to human subjects. Two different lipolysis buffers, differing in the level of surfactant concentrations, were used for digestion of the LFs. The predicted fraction of absorbed dose (Fabs) was calculated by measuring the drug concentration in the micellar phase, obtained after ultra–centrifugation of the lipolysis medium. To determine the fraction of drug dose that escapes metabolism in the gut wall and in the liver (Fg∙Fh), microsomal metabolism stability studies with human intestinal and hepatic microsomes were performed. Clearance values were determined by applying the “in vitro half–life approach”, which is based on the measurement of the first–order rate depletion constant of a drug substrate. The estimated Fabs and Fg∙Fh values were combined for the calculation of the predicted oral bioavailability (Fpredicted). For the model LFs tested, results showed there was a correlation between Fobserved and Fpredicted values only when Fabs was calculated with the buffer characterised by more bio–relevant (lower) surfactant levels. The general accuracy of the predicted values, and the strong correlation shown with the clinical ones, suggests the novel in vitro lipolysis/metabolism approach could satisfactory quantitatively estimate the oral bioavailability of BCS II drugs administered in LFs.